PROTECTION OF FINANCIAL SERVICES AUTHORITY FOR ISSUER COMPANIES THAT WILL BE FORCED DELISTED BY THE STOCK EXCHANGE ACCORDING TO OJK REGULATION NO. 23/POJK.04/2021 - Musa Kevin Putratama Banjarnahor; Budiman Ginting; Sunarmi (Journal of International Islamic Law, Human Right and Public Policy, 2025)
The guidance and supervision actions carried out by the Financial Services Authority (OJK) if unable to prevent the occurrence of force delisting, then force delisting will not only affect the issuer but also affect investors so that this must also be the responsibility of the issuer where the responsibility must be ensured to run well and clearly. This means that the existence of the Financial Services Authority (OJK) in carrying out guidance and supervision of issuers that will be force delisted aims to provide legal protection, namely in the form of guaranteeing the rights of legal subjects (not only issuers whose rights are protected but also investors) and this protection is given to legal subjects so that they can enjoy all the rights granted by law.